LASER SCANNING FOR BIM AND RESULTS VISUALIZATION USING VR - Pavelka jr, K.; Michalík, B. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2019)
Virtual Reality (VR) is a highly topical subject in many branches of science and industry. Thanks to the rapid development and advancement of computer technology in recent years, it can now be used to a large extent, with more detail to show and is now more affordable than before. The use of virtual reality is currently devoted to many disciplines and it can be expected that its popularity will grow progressively over the next few years. The Laboratory of Photogrammetry at the Czech Technical University in Prague is also interested in VR and focuses mainly on documentation and visualization of historical buildings and objects. Our opinion is that in the field of virtual reality there is great potential and extensive possibilities. 3D models of historical objects, primarily created by photogrammetric IBRM technology (image based modelling and rendering) or by laser scanning, gain a completely different perspective in VR. In general, most of the newly designed buildings are now being implemented into BIM. For certain projects, historical buildings or constructions should also have implemented into BIM. As a basic input into BIM, an accurate 3D spatial documentation of the condition is needed with special accent to additional information like engineering networks, materials, etc. Creating BIM is one thing, visualizing a model is another. The historical object is irregular and it is difficult to create its simplified form as the CAD model; it is much easier with modern buildings. The question is always the appropriate type of visualization, where virtual reality can be a very useful technology. So-called game engines such as Unreal engine or Unity are used to create a virtual world. These are highly sophisticated tools that make it possible to create a suitable environment, where you can place created models and then view and analyse them with the help of VR glasses. In our contribution, we would like to show an example of a technology line that allows you to convert an object documented by laser scanning into virtual reality. An older industrial building prepared for future reconstruction was chosen as a case study. This object was scanned by a laser scanner, a 3D model was created and material types and engineering networks were added into the model.